An Analysis of English Teachers’ Perception toward Merdeka Curriculum Implementation at Sekolah Penggerak in Padang Ulak Tanding - Diah Anggun Aprianti; Hamdan; Yulfi (CV Media Inti Teknologi, 2025)
Background: The success of the Independent Curriculum implementation largely depends on teachers’ perceptions, particularly in English language teaching at the elementary level. Aims: This study aims to analyze English teachers’ perceptions of the implementation of the Independent Curriculum in Driving Schools at the elementary level, specifically at SD Negeri 20, SD Negeri 166, and SD Negeri 82 Rejang Lebong in Padang Ulak Tanding. The research focuses on teachers’ understanding and evaluation of the curriculum in terms of its concepts, content, and classroom implementation. Method: A qualitative descriptive method was employed. Data were collected through a 37-item Guttman-scale questionnaire adapted from Perdana (2021) and in-depth interviews with three English teachers. Questionnaire data were analyzed using percentage agreements, while interview data were analyzed thematically to support the findings. Results: The results indicate that English teachers generally have positive perceptions of the Independent Curriculum. Most indicators received approval rates between 80% and 100%, particularly those related to learning flexibility, character education, teacher student collaboration, and the use of varied learning resources. However, lower approval rates (33.3%–66.7%) were found in aspects related to limited training opportunities, assessment difficulties, and challenges in conducting outdoor learning activities. Interview findings further revealed that the curriculum promotes students’ creativity and active participation, although limitations in facilities and teacher readiness remain. Conclusion: English teachers perceive the Independent Curriculum positively and believe it enhances the quality of English language learning. Nevertheless, continuous support, teacher training, and adequate resources are necessary to ensure effective and sustainable implementation.